Preparation method of urushiol-based hydrophobic coating with micro-nano coarse structure
Through the prepolymerization and precipitation polymerization technology of uugol and organic polyamines, a micro-nano rough structure hydrophobic layer is constructed on the surface of different materials, solving the problems of high equipment, high cost and complex process in the existing technology, and achieving high efficiency and low cost Preparation of large-area hydrophobic surfaces.
Patent Information
- Application Number
- CN202411462726.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-19
AI Technical Summary
The prior art has problems such as high equipment requirements, high cost, insufficient process complexity and material universality in preparing rough surfaces of micro-nano structures, making it difficult to achieve simple, efficient and large-area hydrophobic surface preparation.
Urgentol and organic polyamine are used as the main raw materials, and precipitation polymerization is used to construct a hydrophobic coating with a micro-nano rough structure on the surface of different materials. Anhydrous ethanol is used to dissolve urgentol and organic polyamines to form a precursor solution for the deposition reaction. A micro-nano rough structure is formed on the substrate surface by a prepolymerization and precipitation polymerization step.
It realizes simple, efficient and low-cost construction of micro-nano rough hydrophobic layers on the surface of different materials, reducing equipment requirements and process complexity, improving the universality and hydrophobicity of materials, and solving the existing methods on a large-scale preparation efficiency and cost deficiencies.
Smart Images

Figure CN119307176A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material functionalization, and specifically relates to a method for preparing a universal hydrophobic coating. Background Art
[0002] Surface properties are one of the most important physical and chemical properties of materials, and many physical and chemical processes are closely related to the surface properties of materials. Hydrophobic materials developed based on the surface properties of materials show broad application prospects in the fields of surface self-cleaning, anti-icing and anti-fogging, oil-water separation, water-releasing and breathable textiles. A large number of studies have shown that it is difficult to obtain a highly hydrophobic surface simply by reducing the surface energy of ordinary materials. The design and construction of micron- and nano-scale rough structures on the surface of materials is a necessary means to prepare highly hydrophobic materials. This is because the micro-nano rough structure on the surface of the material traps a large amount of air and forms an air film at the solid-liquid interface, which causes water droplets to hang on the surface with micro-nano rough structures and cannot infiltrate.
[0003] In order to construct rough surfaces of micro-nano structures on the surfaces of different materials, researchers at home and abroad have made a lot of attempts. The current representative methods mainly include template method, surface etching method and surface deposition method. Among them, the template method uses the surface of a material with a micro-nano rough structure as a substrate, spreads the active polymer precursor liquid on the substrate surface, forms a continuous whole through casting and curing, and obtains a rough morphology polymer template with the opposite morphology of the substrate after demolding, and then uses this as a template to prepare micro-nano surfaces of different materials. Although this method has low requirements for instruments and equipment, it puts forward extremely high requirements for the precise replication of the micron and nanoscale fine structures of the substrate. The traditional template preparation process still faces great process difficulties and cost pressures in the replication of nano-level precision. In addition, this method often uses natural materials represented by lotus leaves and inorganic porous materials represented by porous alumina as substrate materials, which makes people have less room for regulating the thickness and morphology of the micro-nano structure layer. The surface etching method partially peels off the substrate material through a top-down processing process to form a rough surface with a specific morphology. At present, the etching techniques used for the production of highly hydrophobic surfaces mainly include photolithography, chemical etching and plasma etching, among which photolithography is the most widely studied. Compared with the template method, the surface etching method can directly construct more delicate and regular micro-nano structures on the surface of the material according to the pre-designed pattern. The reported substrate materials cover a variety of types such as silicon wafers, metals, and glass. With the help of chemical modification of low surface energy substances such as fluorosilane, different types of hydrophobic surfaces can be obtained. However, this method has high requirements for processing equipment. In order to achieve high etching accuracy, expensive equipment and harsh working environment are often required. Although the rapid development of femtosecond laser technology in recent years has provided a relatively cheap and convenient photolithography method, it is still difficult to use etching technology to efficiently and large-area prepare micro-nano hierarchical structure surfaces on the surface of macroscopic objects. In contrast to the etching method, the surface deposition method is a method of constructing surface morphology from bottom to top. It mainly forms a layer of micro-nano hierarchical structure coating on the surface of the substrate material by vapor deposition, liquid deposition, hydrothermal growth, electrochemical deposition, etc. Since the deposited material can be different from the substrate material in terms of material, structure, and performance, this method can be used to prepare highly hydrophobic surface materials with more complex and controllable structures and functions. However, this method often requires a more complicated operation process, and has high requirements for reaction conditions and process control; and except for polydopamine, very few compounds can firmly adhere to the surface of different types of materials and gradually deposit to form a micro-nano rough structure layer, and the strong hydrophilicity of dopamine itself also means that this deposited coating needs to be subsequently chemically modified with a hydrophobic modifier, which further increases the complexity of the operation and the cost of preparation. Summary of the invention
[0004] In view of the shortcomings of the existing preparation of rough surfaces of micro-nano structures in terms of equipment and conditions, large-scale preparation efficiency and cost, process complexity, and material universality, the present invention provides a new method for constructing a micro-nano rough hydrophobic layer on the surfaces of different types of materials in a simple, efficient, and low-cost manner. The method uses lacquer phenol and organic polyamines as main raw materials, and constructs a hydrophobic coating with a micro-nano rough structure on the surfaces of different materials through prepolymerization combined with precipitation polymerization.
[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing an urushiol-based hydrophobic coating having a micro-nano rough structure, comprising the following steps: 1) Add urushiol and organic polyamine into anhydrous ethanol, stir and dissolve to form a deposition reaction precursor solution; 2) soaking the substrate in the prepared deposition reaction precursor solution to perform a prepolymerization reaction, so that the urushiol undergoes self-polymerization; 3) After the reaction is completed, the acid regulator is slowly added to the solution under continuous stirring to reduce the pH of the solution to 8-9 for precipitation polymerization. During copolymerization and cross-linking, due to the low solubility of the copolymer in the weak alkaline solution, the copolymer nanoparticles are precipitated from the solution and gradually adhered and deposited on the surface of the substrate to form a micro-nano rough structure coating; 4) The substrate treated in step 3) is taken out from the solution, rinsed with anhydrous ethanol and then dried to obtain a modified substrate having a highly hydrophobic micro-nano rough structure surface coating.
[0006] In the prepolymerization reaction stage of the present invention, the self-polymerization reaction of urushiol is the main reaction. At the same time, since the catechol group contained in urushiol is reducing, a small amount of urushiol is converted into a quinone form under the action of oxygen in ethanol and copolymerizes with organic polyamines. The main product of this stage is oligomeric urushiol, which is soluble in ethanol, so no precipitation is produced. Subsequently, the pH of the solution is reduced to 8-9 by adding an organic acid. At this time, the self-polymerization of urushiol is suppressed, and the copolymerization reaction ratio of urushiol and amine is increased. The organic polyamines and the previously generated oligomeric urushiol are copolymerized and cross-linked. The resulting copolymer product is insoluble in a weakly alkaline ethanol solution. As the degree of crosslinking increases and the pH of the solution decreases, it will be deposited on the surface of the substrate in the form of a precipitate to form a hydrophobic coating with a micro-nano rough structure.
[0007] Furthermore, the viscosity of the urushiol in step 1) is greater than 1500 mPa•s.
[0008] Furthermore, the organic polyamine in step 1) is one or more compounds or polymers soluble in ethanol and containing two or more amine groups, such as hexamethylenediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine, etc.
[0009] Furthermore, in parts by weight, 100 parts of anhydrous ethanol, 1.2-1.8 parts of urushiol, and 0.2-1.2 parts of organic polyamine are used in step 1).
[0010] Furthermore, the substrate in step 2) includes inorganic materials such as glass and ceramics, polymer materials such as plastic and chemical fibers, and natural materials such as cotton, linen, paper, and wood.
[0011] Furthermore, the prepolymerization reaction in step 2) is carried out at a temperature of 15-35° C. and for a time of 1-2 h.
[0012] Furthermore, in step 3), the acid regulator is an organic acid such as acetic acid or citric acid.
[0013] Furthermore, the precipitation polymerization time in step 3) is 1-4 hours.
[0014] Furthermore, in step 4), the drying temperature is 60° C. and the drying time is 1 hour.
[0015] The invention firstly utilizes the solubility of ethanol in urushiol to extract urushiol from raw lacquer as a reaction raw material; then, urushiol and organic polyamine are added to anhydrous ethanol to prepare a deposition reaction precursor solution; then, a substrate is immersed in the deposition reaction precursor solution, and the base catalysis of the organic polyamine is utilized to make the urushiol in the deposition reaction precursor solution self-polymerize to form oligomeric urushiol, and at the same time, the urushiol slowly reacts with the organic polyamine to undergo a Schiff base reaction to undergo binary copolymerization; after the reaction is carried out for a period of time, an acid regulator is slowly added to the solution and continuously stirred to inhibit the self-polymerization of urushiol and promote the copolymerization and cross-linking reaction of the urushiol with amines to form a copolymer product insoluble in ethanol, and at the same time, the reduction in the pH value of the solution further reduces the solubility of the copolymer product in the solution, prompting the copolymer product to precipitate, and at the same time, the morphology of nanoparticles of the copolymer product is controlled, so that the precipitate gradually adheres and deposits on the surface of the substrate to form a micro-nano rough structure coating; finally, the substrate is taken out, cleaned, and dried to promote the complete reaction of the two, so as to obtain a modified substrate with a micro-nano rough structure surface coating with high hydrophobicity.
[0016] The significant advantages of the present invention are: First, the present invention immerses the substrate to be treated in a deposition reaction precursor solution, and forms a micro-nano rough structure coating with a micron-scale continuous skeleton and nano-scale spherical protrusions on the surface of the substrate by means of precipitation polymerization and adhesion deposition. The preparation process is time-saving and the reaction conditions are mild. It does not require complex and expensive equipment and harsh reaction conditions to complete large-area material surface modification at one time, effectively solving the problems of low efficiency and high cost in the existing methods for large-scale preparation of micro-nano rough structure hydrophobic surfaces.
[0017] Second, the present invention only needs to prepare a deposition precursor solution with simple ingredients, and can gradually carry out steps such as lacquer phenol-polyamine copolymerization, precipitation of nanoparticles, and substrate surface adhesion deposition on different types of materials in a "one-pot" process in a reaction container, without the need to switch other reaction systems and reaction containers in the middle, and the microstructure of the deposited coating can be conveniently regulated by the pH value of the solution. After the deposition is completed, a high hydrophobic effect can be achieved without chemical modification such as silane modification, thereby solving the problems of complex process and high operation requirements in the existing methods.
[0018] Third, the main raw material urushiol used in the present invention contains a large number of catechol groups, which can be firmly attached to the surfaces of various types of materials and has stronger substrate universality than existing methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a reaction mechanism diagram of the present invention using urushiol-organic polyamine to construct a micro-nano rough structure coating.
[0020] Figure 2 The sample image, water contact angle and surface SEM image of the urushiol-triethylenetetramine (pH=9) deposition modified filter paper prepared in Example 1.
[0021] Figure 3 The sample image, water contact angle and surface SEM image of the urushiol-triethylenetetramine (pH=8.5) deposition modified filter paper prepared in Example 2.
[0022] Figure 4 The sample image, water contact angle and surface SEM image of the urushiol-triethylenetetramine (pH=8) deposition modified filter paper prepared in Example 3.
[0023] Figure 5 The sample image, water contact angle and surface SEM image of the urushiol-diethylenetriamine (pH=8) deposition modified polyester non-woven fabric prepared in Example 4.
[0024] Figure 6 The sample image, water contact angle and surface SEM image of the urushiol-hexamethylenediamine (pH=8) deposition-modified glass slide prepared in Example 5.
[0025] Figure 7 The infrared spectrum and XPS spectrum of the urushiol-hexamethylenediamine copolymer deposit obtained in Example 5 are shown.
[0026] Figure 8 The sample image, water contact angle and surface SEM image of the urushiol-polyethyleneimine (pH=8) deposition modified cotton cloth prepared in Example 6.
[0027] Fig. 9 The sample image, water contact angle and surface SEM image of the lacquer phenol-hexamethylenediamine thermally cured modified glass slide prepared in Control Example 1.
[0028] Fig.10 This is the sample image, water contact angle and surface SEM image of the modified glass slide prepared in Control Example 2 by heat curing lacquer phenol-hexamethylenediamine in a mixed solvent of ethanol and water. DETAILED DESCRIPTION
[0029] A method for preparing an urushiol-based hydrophobic material having a micro-nano rough structure, comprising the following steps: 1) Add raw lacquer to anhydrous ethanol at a volume ratio of 5:1, stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol, let stand for stratification, and then evaporate the ethanol from the urushiol ethanol solution to obtain purified urushiol. After continuous stirring until the viscosity is greater than 1500mPa•s, transfer the mixture into a container and seal it for storage; 2) Add 1.2-1.8 parts of urushiol and 0.2-1.2 parts of organic polyamine to 100 parts of anhydrous ethanol by weight, and stir to dissolve to form a deposition reaction precursor solution; 3) Soaking the substrate in the prepared deposition reaction precursor solution and prepolymerizing at 15-35°C for 1-2 hours to allow the urushiol to self-polymerize; 4) After the reaction is completed, the acid regulator is slowly added to the solution under continuous stirring to reduce the pH of the solution to 8-9, and precipitation polymerization is performed for 1-4 hours. At the same time, the pH value change is used to cause the copolymer nanoparticles to precipitate from the solution and gradually adhere to and deposit on the surface of the substrate to form a micro-nano rough structure coating; 5) The substrate treated in step 4) is taken out from the solution, rinsed with anhydrous ethanol and dried at 60° C. for 1 hour to allow the sediment to react completely, thereby obtaining a modified substrate having a highly hydrophobic micro-nano rough structure surface coating.
[0030] The organic polyamine is one or more compounds or polymers soluble in ethanol and containing two or more amine groups, such as hexamethylenediamine, diethylenetriamine, triethylenetetramine, and polyethyleneimine. The substrate includes inorganic materials such as glass ceramics, polymer materials such as plastic chemical fibers, and natural materials such as cotton, linen, paper, and wood. The acid regulator is an organic acid such as acetic acid and citric acid.
[0031] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0032] Example 1 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1800 mPa·s. Then transfer it to a sealed container for storage.
[0033] (2) Add 1.2 g of urushiol and 0.4 g of triethylenetetramine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0034] (3) Place the deposition reaction precursor solution in a culture dish, soak the qualitative filter paper in the deposition reaction precursor solution, seal the container with a plastic wrap with small holes, and then place the culture dish in a 15°C oven to react for 2 hours. Then, add acetic acid to the deposition solution under constant stirring to adjust the pH of the solution to 9. After the addition is completed, continue the reaction and deposition for 2 hours.
[0035] (4) Take out the treated filter paper, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0036] like Figure 2 It can be seen that due to the higher pH value in this embodiment, the urushiol self-polymerization reaction occupies a major position in the reaction, and the product has a low degree of cross-linking, resulting in a higher solubility, so that the surface of the filter paper is an amorphous coating formed by large-area bonding of urushiol and triethylenetetramine. Although the coating has a bonding layer with a length of 5-8 μm and spherical protrusions with a diameter of about 800 nm, it has only preliminary micro-nano rough structure characteristics as a whole, so it has moderate hydrophobicity and a water contact angle of 121°.
[0037] Example 2 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1800 mPa·s. Then transfer it to a sealed container for storage.
[0038] (2) Add 1.2 g of urushiol and 0.4 g of triethylenetetramine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0039] (3) Place the deposition reaction precursor solution in a culture dish, soak the qualitative filter paper in the deposition reaction precursor solution, seal the container with a plastic wrap with small holes, and then place the culture dish in a 15°C oven to react for 2 hours. Then, add acetic acid to the deposition solution under constant stirring to adjust the pH of the solution to 8.5. After the addition is completed, continue the reaction and deposition for 2 hours.
[0040] (4) Take out the treated filter paper, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0041] like Figure 3It can be seen that in this embodiment, since the pH is lowered to 8.5, the copolymerization reaction of urushiol-amine increases in the reaction proportion, and the degree of cross-linking of the product increases, resulting in lower solubility. Therefore, a small amount of bonded coral-like coating formed by the deposition of urushiol-triethylenetetramine is obtained on the surface of the filter paper. The coating consists of an adhesive layer with a length of 3-4 μm and a large number of spherical protrusions with a diameter of about 500-600 nm, and has obvious micro-nano rough structure characteristics. Therefore, it is highly hydrophobic and has a water contact angle of 132°.
[0042] Example 3 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1800 mPa·s. Then transfer it to a sealed container for storage.
[0043] (2) Add 1.2 g of urushiol and 0.4 g of triethylenetetramine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0044] (3) Place the deposition reaction precursor solution in a culture dish, soak the qualitative filter paper in the deposition reaction precursor solution, seal the container with a plastic wrap with small holes, and then place the culture dish in a 15°C oven to react for 2 hours. Then, add acetic acid to the deposition solution under constant stirring to adjust the pH of the solution to 8. After the addition is completed, continue the reaction and deposition for 2 hours.
[0045] (4) Take out the treated filter paper, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0046] like Figure 4 It can be seen that in this embodiment, since the pH is lowered to 8, the copolymerization reaction occupies a major position in the reaction, and the product has a high degree of cross-linking, resulting in very low solubility. Therefore, a coral-like coating formed by the deposition of urushiol-triethylenetetramine is obtained on the surface of the filter paper. The coating is composed of a coral-like skeleton with a length of 2-3 μm and a large number of spherical protrusions with a diameter of 300-400 nm, and has obvious micro-nano rough structure characteristics. Therefore, it is highly hydrophobic and the water contact angle can reach 144°.
[0047] Example 4 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1600 mPa·s. Then transfer it to a sealed container for storage.
[0048] (2) Add 1.2 g of urushiol and 1.2 g of diethylenetriamine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0049] (3) Use a culture dish to hold the deposition reaction precursor liquid, soak the polyester non-woven fabric in the deposition reaction precursor liquid, seal the container mouth with a plastic wrap with small holes, and then place the culture dish in a 25°C oven to react for 1 hour. Then, add acetic acid to the deposition liquid under constant stirring to adjust the solution pH to 8. After the addition is completed, continue the reaction deposition for 4 hours.
[0050] (4) Take out the treated polyester non-woven fabric, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0051] like Figure 5 It can be seen that in this embodiment, due to the lower pH value, the copolymerization reaction occupies a major position in the reaction, and the high degree of cross-linking of the product leads to very low solubility. Therefore, the surface of the non-woven fabric is obtained by a coral-like coating formed by the deposition of urushiol-diethylenetriamine. The coating is composed of a coral-like skeleton with a length of 3-4 μm and a large number of spherical protrusions with a diameter of 400-500 nm, and has obvious micro-nano rough structure characteristics. Therefore, it is highly hydrophobic and the water contact angle can reach 141°.
[0052] Example 5 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1900 mPa·s. Then transfer it to a sealed container for storage.
[0053] (2) Add 1.8 g of urushiol and 0.6 g of hexamethylenediamine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0054] (3) Use a culture dish to hold the deposition reaction precursor liquid, immerse the glass slide in the deposition reaction precursor liquid, seal the container mouth with a plastic wrap with small holes, and then place the culture dish in a 35°C oven to react for 1.5 hours. Then, add citric acid to the deposition liquid under constant stirring to adjust the solution pH to 8. After the addition is completed, continue the reaction deposition for 3 hours.
[0055] (4) Take out the treated slide, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0056] like Figure 6It can be seen that in this embodiment, due to the lower pH value, the copolymerization reaction occupies a major position in the reaction, and the high degree of cross-linking of the product leads to very low solubility. Therefore, a coral-like coating formed by the deposition of urushiol-hexamethylenediamine is obtained on the surface of the glass slide. The coating is composed of a coral-like skeleton with a length of 4-6 μm and a large number of spherical protrusions with a diameter of 400-600 nm, and has obvious micro-nano rough structure characteristics. Therefore, it is highly hydrophobic and has a water contact angle of 129°.
[0057] Figure 7 The infrared spectrum and XPS spectrum of the obtained urushiol-hexamethylenediamine copolymer sediment are shown in Figure 1. As can be seen from the figure, compared with pure urushiol, the infrared spectrum of the copolymer at 1520 cm -1 The imine absorption peak of C=N appears at 1590cm -1 The CN absorption peak at the urethane foam was also strengthened, indicating that urushiol and hexamethylenediamine underwent binary copolymerization with the help of Schiff base reaction. At the same time, the XPS spectrum of the copolymer also showed the C=N / CN absorption peak, while pure urushiol only contained C, H, and O elements and did not contain N element, which further verified the occurrence of copolymerization.
[0058] Example 6 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 2000 mPa·s. Then transfer it to a sealed container for storage.
[0059] (2) Add 1.8 g of urushiol and 0.2 g of polyethyleneimine to 100 mL of anhydrous ethanol and stir to dissolve to prepare a deposition reaction precursor solution.
[0060] (3) Place the deposition reaction precursor liquid in a culture dish, soak the cotton cloth in the deposition reaction precursor liquid, seal the container mouth with a plastic wrap with small holes, and then place the culture dish in a 35°C oven to react for 2 hours. Then, add acetic acid to the deposition liquid under constant stirring to adjust the solution pH to 8. After the addition is completed, continue the reaction deposition for 1 hour.
[0061] (4) Take out the treated cotton cloth, rinse it with anhydrous ethanol, and dry it in an oven at 60°C for 1 hour to allow the sediment to react completely.
[0062] like Figure 8 It can be seen that in this embodiment, due to the lower pH value, the copolymerization reaction occupies a major position in the reaction, and the high degree of cross-linking of the product leads to very low solubility. Therefore, the surface of the cotton cloth obtains a coral-like coating formed by the deposition of urushiol-polyethyleneimine. The coating is composed of a coral-like skeleton with a length of 2-3 μm and a large number of spherical protrusions with a diameter of 300-500 nm, and has obvious micro-nano rough structure characteristics. Therefore, it is highly hydrophobic and the water contact angle can reach 143°.
[0063] Comparative Example 1 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1900 mPa·s. Then transfer it to a sealed container for storage.
[0064] (2) Add 10 mL of anhydrous ethanol, 1.8 g of urushiol, and 0.6 g of hexamethylenediamine into a beaker and stir to prepare a urushiol-hexamethylenediamine mixed solution.
[0065] (3) The mixed solution was coated on the surface of a glass slide and placed in an oven at 120°C for 24 hours for drying and solidification to obtain a lacquer phenol-hexamethylenediamine modified glass slide with a dense and smooth surface structure.
[0066] like Fig. 9 It can be seen that in this control example, due to the use of a mixed solution coating method for drying and curing, a micro-nano rough structure coating cannot be obtained and only a dense and smooth microscopic surface morphology can be obtained, and its water contact angle is only 90°.
[0067] Comparative Example 2 (1) Add 100 mL of raw lacquer to 500 mL of anhydrous ethanol and stir thoroughly to dissolve the urushiol in the raw lacquer in the ethanol. After standing for stratification, remove the ethanol from the urushiol ethanol solution by rotary evaporation. Place the purified urushiol in a container and stir continuously until its viscosity reaches 1900 mPa·s. Then transfer it to a sealed container for storage.
[0068] (2) Add 8 mL of anhydrous ethanol, 2 mL of deionized water, 1.8 g of urushiol and 0.6 g of hexamethylenediamine into a beaker and stir to prepare a urushiol-hexamethylenediamine mixed solution.
[0069] (3) The mixed solution was coated on the surface of a glass slide and placed in an oven at 120°C for 24 hours for drying and solidification to obtain a lacquer phenol-hexamethylenediamine modified glass slide with a dense surface structure.
[0070] like Fig.10 It can be seen that although the introduction of water can cause a certain solubility change of the reactants when drying, it can only form wrinkles on the macroscopic appearance but cannot produce a microscopic micro-nano rough structure surface, and its water contact angle is only 92°.
[0071] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an urushiol-based hydrophobic coating having a micro-nano rough structure, characterized in that: The steps include: 1) Add urushiol and organic polyamine into anhydrous ethanol, stir and dissolve to form a deposition reaction precursor solution; 2) Immersing the substrate in the prepared deposition reaction precursor solution to perform a prepolymerization reaction; 3) After the reaction is completed, an acid regulator is added under continuous stirring to reduce the pH of the solution to 8-9 for precipitation polymerization, so that the copolymer nanoparticles are precipitated from the solution and gradually adhere to and deposit on the surface of the substrate to form a micro-nano rough structure coating; 4) The substrate treated in step 3) is taken out from the solution, rinsed with anhydrous ethanol and then dried to obtain a modified substrate having a highly hydrophobic micro-nano rough structure surface coating.
2. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1, characterized in that: In parts by weight, 100 parts of anhydrous ethanol, 1.2-1.8 parts of urushiol, and 0.2-1.2 parts of organic polyamine are used in step 1).
3. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1 or 2, characterized in that: The viscosity of the urushiol is greater than 1500 mPa•s.
4. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1 or 2, characterized in that: The organic polyamine is one or more compounds or polymers that are soluble in ethanol and contain two or more amine groups.
5. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1, characterized in that: The temperature of the prepolymerization reaction in step 2) is 15-35°C and the time is 1-2h.
6. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1, characterized in that: Step 3) The acid regulator is an organic acid.
7. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1, characterized in that: Step 3) The precipitation polymerization time is 1-4 hours.
8. The method for preparing the urushiol-based hydrophobic coating having a micro-nano rough structure according to claim 1, characterized in that: Step 4) The drying temperature is 60°C and the drying time is 1 hour.
Citation Information
Patent Citations
UV-cured urushiol-based hyperbranched super-amphiphobic anti-corrosion coating and preparation method thereof
CN110272679A
Super-hydrophobic self-cleaning coating, preparation thereof, coating based on super-hydrophobic self-cleaning coating and application
CN117050659A
Urushiol thin film and method for preparing the same
KR1020170041957A